1993
DOI: 10.1002/bjs.1800800933
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection with normothermic ischaemia exceeding 1 h

Abstract: A retrospective study was made of 34 patients who underwent major liver resection with a single period of vascular occlusion exceeding 60 min. The liver remnant was normal in all cases. Vascular occlusion was achieved by continuous portal triad clamping (15 patients), hepatic vascular exclusion (15) or a sequential combination of both procedures (four). Liver cooling was not used. The mean (s.e.m.) duration of continuous normothermic liver ischaemia was 73.6 (2.5) (range 60-127) min. The mean (s.e.m.) amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
9

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 15 publications
0
52
1
9
Order By: Relevance
“…Hepatocytes can stand against ischemia for 30-60 minutes. Following a 60 minutes of ischemia, free oxygen radicals starts to increase at the fifth minute and reaches to maximum level at the 15th minute [11]. Suzuki et al reported that maximum injury occurs after 90 minutes of ischemia followed by a 60 minutes of reperfusion and thereby they have reported that the injury is proportional with the time of I/R injury duration [12].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes can stand against ischemia for 30-60 minutes. Following a 60 minutes of ischemia, free oxygen radicals starts to increase at the fifth minute and reaches to maximum level at the 15th minute [11]. Suzuki et al reported that maximum injury occurs after 90 minutes of ischemia followed by a 60 minutes of reperfusion and thereby they have reported that the injury is proportional with the time of I/R injury duration [12].…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, variações do procedimento operatório como a oclusão das estruturas vasculares sem o clampeamento do ducto biliar, ou a utilização de substâncias protetoras da lesão de isquemia, como a NAC, tem efeitos no sucesso do procedimento e no pós-operatório. Isto ocorre porque a lesão de isquemia evolui à morte celular e perda da função do órgão, decorrente do colapso na produção de energia pela cadeia respiratória, mobilização dos depósitos de cálcio e perda da função das membranas 2,10 .…”
Section: Discussionunclassified
“…A manobra de Pringle tem sido empregada pelos cirurgiões nas ressecções e traumas hepáticos, promovendo uma isquemia durante o ato operatório. Dependendo do tempo de oclusão do pedículo hepá-tico ocorre lesão tecidual que evolui à insuficiência hepática 2 . A isquemia hepática total produzida por esta manobra tem sido utilizada nos estudos em animais de experimentação associada com a derivação vascular, no intuito de prevenir os eventos patológicos em outras áreas, que advêm dessa isquemia, tais como a congestão esplâncnica e a isquemia intestinal, com conseqüente endotoxemia, que evolui com o choque e a morte do animal 1,3 .…”
Section: Introductionunclassified
“…At present, it is generally accepted that liver resection performed under intermittent warm ischema is a safe and well-tolerated modality in patients with and without cirrhotic livers [20] . Huguet and others showed that hepatocytes could tolerate normothermic ischemia in excess of 1 hour, and ischemia up to 2 hour without major detrimental effects other than transient hepatic failure has never been reported [21,22] . Others suggested that the risks related to hemorrhage were of greater concern than those related to the time of ischemia.…”
Section: Discussionmentioning
confidence: 99%